Evaluation of myocardial performance index in smokers (Annals of Medical Research, 2021)
Aim: The aim of this study was to evaluate MPI and left ventricular (LV) functions in patients without cardiac risk factors except smoking. Smoking is associated with increased cardiovascular events. Myocardial performance index (MPI) is a noninvasive tissue doppler technique that provides information about left ventricular systolic and diastolic functions.Material and Methods: A total of 50 smokers and 50 healthy volunteers were consequently included in the study. All participants underwent echocardiographic examinations, including MPI measurements.Results: We found that MPI values were significantly higher in the smoker group (0.52 ± 0.08, 0.42 ± 0.07, p 0.001). E wave (0.73 ± 0.18, 0.84 ± 0.25, p = 0.018), IVRT (77.52 ± 11.90, 61.80 ± 12.85, p 0.001), IVCT (60.84 ± 15.67, 53.16 ± 10.68, p = 0.005) values were significantly lower in the control group.There was a positive correlation between packet-year and MPI (r = 0.525, p0.001)Conclusion: In our study, we observed increased MPI in smokers, which was shown to be associated with left ventricular function. We think that MPI could be used as an easy method to determine subclinical left ventricular dysfunction in healthy smokers.